ITC in the School of Nursing at the Valle University: A transformative experience (Colombia Medica, 2024)
Introduction: In order to spread the experience of the School of Nursing in the use of innovative strategies, which facilitate the formation of the students in higher education, with difficult access to the education classroom for fulfilling diverse roles in society; this article presents this systematized strategy, doing a tour from the years 60 up to the use of ITC at present.Methods. Historical documents were collected from the School of Nursing, research papers, systematization and evaluation of students and teachers related to the topic.Results. The methodologies used according to the state of technology as well as gains and areas for improvement both teachers and students with effective use of ITC.Conclusions. One of the main factors for the successful implementation of ITC in higher education is the favorable perception of teachers in front of them, because even though some teachers do not consider it necessary to introduce new ways of teaching and learning, many others are willing and committed to innovate and propose new pedagogical challenges using the resources provided by these technologies. The results of this experience show that the technological and pedagogical innovation is key to expanding coverage, undergraduate and postgraduate nursing as well as for the strengthening to discipline, the conceptualization and the practice of the human care.